Analysis of supply chain management of horticultural nurseries - Rajasree P. (Department of Agricultural Economics, College of Horticulture, 2016)
Success of any horticultural production programme mainly depends on the quality of seeds and planting materials used for the production. Unavailability of adequate quantity of quality seeds and planting materials is one of the most important problems affecting the development of the horticulture sector. Even though plant nursery industry is considered as a sunrise industry in our country, only less attention is given in monitoring its activities, quality control and also in evaluating its role in the economy. The present study attempted to understand the supply chain management, income and employment potential and constraints of horticultural nursery business in the study area. Thrissur district, which is considered as the hub of nursery business in Kerala, was purposively selected as the location of study. 40 nurseries were selected by simple random sampling method. The sample nurseries were classified on the basis of their operational area as C-1 (<0.5 acre), C-2 (0.5 acre- 2 acre) and C-3 (>2 acre). Accordingly, 52.5 per cent of the nurseries in the study area come under the category C-2, followed by C-1(25%) and C-3(22.5%). Pre-tested interview schedules were used to collect information from sample nurseries. Secondary data were collected from Krishi Bhavan, Principal Agricultural Office and various published sources. The nursery registration status in the study area showed that only 27.5 per cent of the sample nurseries were registered nurseries. All the nurseries under the category C-1, 66.66 per cent of the nurseries under C-2 and 55.55 per cent of the nurseries under C-3 were not registered. Supply chain mapping was done to identify the supply chains of horticultural nurseries in the study area. The identified supply chains were Chain 1: Sample nursery – Customers (direct or indirect), Chain 2: Farmers/Households – Agent – Sample nursery – Customers (direct or indirect), Chain 3: Satellite nursery – Sample nursery – Customers (direct or indirect), Chain 4: Other nurseries – Sample nursery – Customers (direct or indirect) and Chain 5: Other nurseries – Agent – Sample nursery – Customers (direct or indirect). Chain 1, 4 and 5 are the most common supply chains in the study area. Chain 1: Sample nursery - Customers This is the supply chain in which the plants produced in the nursery are supplied to the ultimate consumer. This chain can be of two types, i.e., direct selling of planting materials to customers or selling indirectly through garden setting contractors or other nurseries. Here garden setting contractors act as the middle men between the nurseries and customers (Homesteads, Corporates etc.) or other nurseries will purchase from the sample nursery and resell the planting materials to customers. Chain 2: Farmers/ Households - Agent - Sample nursery – Customers Here the mother plant source is not available in the nursery. So, in this supply chain an agent will be there for the collection of planting materials from mother plants sources from farmers and households. This supply chain is most common in case of coconut, pepper etc. Here the agent will collect coconut, pepper cuttings etc. for seedling purpose from farmers and households and provides to the nurseries and the nurseries will use them for making seedlings for sale. The main disadvantage of this supply chain is that mother plants of unknown pedigree may be used for the propagation. This supply chain will affect the quality of seedlings produced, if the mother plants are collected from unrecognised sources. This chain also can be of direct or indirect. Channel 3: Satellite nurseries – Sample nursery - Customers Here in this supply chain the large scale nurseries will identify those farmers with good quality mother plants and assign them with the duty of producing seedlings from the mother plants they have for the nurseries. Another method in this supply chain is that the nursery owner will assign the duty of the production of seedlings to private individuals and all the inputs and mother plants are also provided by the nursery owner himself. Chain 4: Other nurseries (inside and outside Kerala and outside India) -Sample nursery -Customers In this supply chain, the nurseries in the study area are purchasing potted plants from other nurseries inside and outside Kerala. This is a whole sale supply chain. In this supply chain the nursery owners will directly purchase plants from other nurseries without the help of any intermediaries or order will be placed to other nurseries through mail or phone call. The purchased plants will be resold to their customers. Chain 5: Other nurseries (inside and outside Kerala) - Agent – Sample Nursery -Customers This is the most common supply chain identified in the study area through which bulk volume of plants are transacted. This supply chain is seen in case plants transacted inside India only. In this supply chain an agent/ middlemen will be there in between other nurseries and the sample nurseries in the study area. The nurseries in the study area will contact the middlemen for the purchase of plants from other nurseries. The following supply chains are identified for public sector nurseries. Chain 1: Sample nursery – Customers It is similar to the Chain 1 of private sector nurseries. Chain 2: Farmers/Krishibhavan/Government agencies (Collection of planting materials from good quality mother plants) – Sample nursery -Customers Public sector nurseries are having their own mother plants sources for almost all the plants produced in the nursery. These nurseries will collect planting materials from recognised farmers through Krishi Bhavan and also through other government agencies for which they don’t have good source of mother plants. Chain 3: Sample nursery - Government agencies – Farmers (through government schemes) In this chain government agencies will collect seedlings from the government nurseries for distributing among the farmers through various government schemes. This chain is observed in case of registered private sector nurseries also. The efficiency of supply chain was measured using the model proposed by Aramyan et al., 2006 with suitable modifications. Including the dimensions of efficiency, flexibility and quality of planting materials in the chains, a Supply Chain Performance Index (SCPI) was developed. The SCPI of the chain consisting of plants produced in the nursery was 0.85 and that of plants purchased from other nurseries was 0.80. Hence, out of the two most common supply chains in the study area, the chain with own production of plants was identified slightly more efficient than the supply chain involving purchase of plants from other nurseries. Employment generation and income from the nursery business was also worked out. Nurseries under the category C-3 on average generated 5373.33 man-days per year followed by C-2 1040 man-days per year and C-1 605.8 man-days per year. The estimated BC ratio of nurseries under C-3 was 1.92, followed by 1.65 in C-2 and 1.56 in C-1. The nursery business in the study area was identified as a profitable business and they contribute substantially to the income and employment generation in the locality. According to the nursery owners, market competition was the major constraint affecting their business, followed by unavailability of raw materials and cost of raw materials. Labour shortage, land availability, pest and diseases and weather related issues were the other problems faced by the nursery owners in the study area. Horticultural nurseries being the providers of seed material for long term investments in farming, supply of quality planting material is of utmost importance. Hence, measures have to be taken to monitor and evaluate the activities in the nurseries in order to ensure the quality of planting materials produced in the nursery. Lack of proper registration and monitoring mechanism leading to the proliferation of nurseries and unhealthy management were identified as major issues in the horticultural nursery business. Horticultural nursery business should be under the ambit of regulation and control and more effective implementation of the rules regarding plant nursery business in our country is suggested. There should be a well-defined mechanism for monitoring the activities in the nurseries and maintaining the quality of planting materials produced in the nurseries. A coordinated effort starting right from the grass root level organizations like Panchayats and Department of Agriculture is required in this regard. Training programmes and seminars in plant nursery management should be organized for nursery owners and labourers in the nursery. Collaborative efforts from the part of government agencies and private nursery owners for the transfer of new techniques in plant propagation, nursery management practices, and record keeping should be there. Capacity building programmes have to be undertaken to improve the nursery management skills and planting material production skills.